2013
DOI: 10.1159/000354492
|View full text |Cite
|
Sign up to set email alerts
|

Neural Ganglioside GD2+Cells Define a Subpopulation of Mesenchymal Stem Cells in Adult Murine Bone Marrow

Abstract: Background/Aims: Due to the lack of specific markers, the isolation of pure mesenchymal stem cells (MSCs) from murine bone marrow remains an unsolved problem. The present study explored whether the neural ganglioside GD2 could serve as a single surface marker to uniquely distinguish murine bone marrow MSCs (mBM-MSCs) from other marrow elements. Methods: Immunocytochemistry and flow cytometry, in combination with quantitative RT-PCR, were used to identify the expression of GD2 on culture-expanded mBM-MSCs. GD2<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Both SCs [41] and CSCs were identified since they were found to express specific cell-surface markers. A lot of studies have identified CSC markers across a variety of solid cancers, but relatively few of these markers have been studied in HNSCC, and the putative CSCs from HNSCC have not been well characterized [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Both SCs [41] and CSCs were identified since they were found to express specific cell-surface markers. A lot of studies have identified CSC markers across a variety of solid cancers, but relatively few of these markers have been studied in HNSCC, and the putative CSCs from HNSCC have not been well characterized [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these stromal‐derived lipids has been demonstrated in both myelopoiesis and lymphopoiesis in vitro and in vivo . BM stromal cells express gangliosides in both humans and mice . Xu et al .…”
Section: Lipid Metabolism In Haematopoiesismentioning
confidence: 99%
“…Xu et al . have shown that ganglioside‐expressing murine stromal cells exhibit a stronger proliferative phenotype . These cells differentiate more readily into adipocytes and osteoblasts, cellular components of the BM niche that support haematopoiesis and are likely leptin receptor + mesenchymal stromal cells or a subset thereof (Figure aii).…”
Section: Lipid Metabolism In Haematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…Skin SCC causes a lot of mortality yearly, which requires a better understanding of the molecular carcinogesis of skin SCC for developing efficient therapy [1,2]. Ginsenoside Rh2 (GRh2) is a characterized component in red ginseng, and has proven therapeutic effects on inflammation [3] and a number of cancers [4][5][6][7][8][9][10][11][12][13][14], whereas its effects on the skin SCC have not been examined.…”
Section: Introductionmentioning
confidence: 99%